2010
DOI: 10.14214/sf.158
|View full text |Cite
|
Sign up to set email alerts
|

Family forest owners’ opinions about forest management in northern Finland

Abstract: Forest management guidelines changed at the end of the 1990's in Finland. Biodiversity, visual landscape, water systems, and different forms of forest use are now better taken into account. The objectives, outdoor recreation motives, and attitudes towards the present forest management activities of the non-industrial private forest owners called family forest owners in this article, whose forest holdings are located in northern Finland, were studied. In addition, a forest owner typology based on the above-ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Further, another interesting finding of article II is that the academically educated NIPF owners give aesthetics and conservation more importance than the timber production objective. Uliczka et al (2004), Hallikainen et al (2010) and Koskela (2011) also indicated a connection between more highly educated forest owners and pro-conservation values.…”
Section: Contribution Of the Thesis And Discussionmentioning
confidence: 99%
“…Further, another interesting finding of article II is that the academically educated NIPF owners give aesthetics and conservation more importance than the timber production objective. Uliczka et al (2004), Hallikainen et al (2010) and Koskela (2011) also indicated a connection between more highly educated forest owners and pro-conservation values.…”
Section: Contribution Of the Thesis And Discussionmentioning
confidence: 99%
“…These working lands can be a major or supplemental source of income for their owners or can be a hobby-like activity (e.g., Sorice et al 2012, Urquhart et al 2012. Other than income generation, ownership motives can include aesthetics, recreation, community values, conservation, hunting or fishing, and residential (Hallikainen et al 2010, Plieninger et al 2012, Howley 2013. Not surprisingly, studies on landowners that are likely to use their land for income generation, have found that financial incentives, especially their size and conditions, are important when deciding on enrolment in conservation programs (Koontz 2001, Kabii and Horwitz 2006, Sorice et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with results by Koskela (2011), who found that highly educated forest owners in Finland are more willing to voluntarily protect biodiversity. Hallikainen et al (2010) have also found a link between highly educated NIPF owners and their pro-conservation values.…”
Section: Contribution Of This Thesismentioning
confidence: 87%